Advertising as a claim for the media: the case of Madison in The New York Times and its relationship with some Spanish newspapers - Marcos Recio, Juan Carlos; Hernández Ruiz, Alejandra (Revista General de Información y Documentación, 2017)
Advertising has not only commercial value, but also it reflects a social environment of a bygone society. Therefore, its conservation is critical. This text explains the experience of Madison, a tool designed by The New York Times to create, collaboratively, a digital archive of advertising, in this case, from the main newspaper in the world. In addition, advertising heritage preservation in a sample of Spanish newspapers is studied. It is shown how Madison works, its presentation and how readers can contribute to its improvement. To know the situation of the Spanish newspapers regarding the digitization of their archives, a self-administered questionnaire is designed and contacts are with the persons in charge of information archive or commercial directors of the newspapers with the higher advertising revenues. In the Spanish case, none of the media gives special attention to advertising heritage conservation. Technical and economic barriers impede their differential treatment of information content, so that just accidentally old advertising pieces can be accessible among the set of pages of the newspaper.
Keywords: Advertising; Advertising Heritage; Documentary Analysis; Media; Madison; The New York Times.